Sintering and mass transport features of (Sn,Ti)O2 polycrystalline ceramics - Bueno, Paulo Roberto [UNESP]; Leite, E. R.; Bulhoes, L. O S; Longo, Elson [UNESP]; Paiva-Santos, C. O. [UNESP] (Elsevier, 2003)
Different (Sn,Ti)O2 compositions were sintered at 1450 °C for 2 h with the purpose of investigating their sintering and mass transport properties. Highly dense ceramics were obtained and their structural properties studied by X-ray diffraction and scanning electron microscopy. The changes in lattice parameters were analyzed by the Rietveld method and two mass transport mechanisms were observed during sintering in different temperature ranges, evidenced by the linear shrinkage rate as a function of temperature. The effect of the concentration of TiO2 on mass transport and densiffication during sintering was analyzed by considering the intrinsic defects. System densiffication was attributed to a mass transport mechanism in the SnO2 matrix, caused by the presence of TiO2, which formed a solid solution phase. The change in the mass transport mechanism was attributed to chemical bonding between SnO2 and TiO2, which improves ionic difusion as the concentration of TiO2 increased in (Sn,Ti)O2 compositions. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: (Sn,Ti)O2; Microstructure- final; Sintering; Chemical bonds; Crystal defects; Densification; Lattice constants; Mass transfer; Phase composition; Polycrystalline materials; Scanning electron microscopy; Solid solutions; X ray diffraction; Intrinsic defects; Ceramic materials; ceramics; mass transfer; sintering